2020
DOI: 10.1017/s1368980020003547
|View full text |Cite|
|
Sign up to set email alerts
|

Associations between nutrient intakes and dietary patterns with different sarcopenia definitions in older Australian men: the concord health and ageing in men project

Abstract: Objective: To assess the associations between nutrient intake and dietary patterns with different sarcopenia definitions in older men. Design: Cross-sectional study. Setting: Sarcopenia was defined using the Foundation for the National Institutes of Health (FNIH), the European Working Group on Sarcopenia in Older People (EWGSOP) and the European Working Group on Sarcopenia in Older People 2 (EWGSOP2). Dietary adequacy of fourteen nutrients was assessed by comparing part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
2
15
0
Order By: Relevance
“…However, there was no significant association between protein intake and sarcopenia prevalence in the present study (Table 2). In agreement with the present findings, some observational studies have found no association between the amounts of daily protein intake and sarcopenia or frailty, because the average daily protein intake was relatively high compared to the 0.83 g/kg BW/day recommended by the World Health Organization [52,53], and these associations would be dependent on the definition of sarcopenia [54].…”
Section: Discussionsupporting
confidence: 90%
“…However, there was no significant association between protein intake and sarcopenia prevalence in the present study (Table 2). In agreement with the present findings, some observational studies have found no association between the amounts of daily protein intake and sarcopenia or frailty, because the average daily protein intake was relatively high compared to the 0.83 g/kg BW/day recommended by the World Health Organization [52,53], and these associations would be dependent on the definition of sarcopenia [54].…”
Section: Discussionsupporting
confidence: 90%
“…The positive association between protein intake and the ATHLOS Healthy Ageing Scale in our cohort is in line with studies which investigated the relationship of diet with other measures of ageing [15,[18][19][20][21][22]36,37]. In cross-sectional studies, lower dietary protein intake was associated with frailty in elderly Japanese women [36], in adults in Spain [19] and with sarcopenia in elderly Belgians [18], or in Australian men [20].…”
Section: Discussionsupporting
confidence: 89%
“…In previous studies concerning the relationship between dietary macronutrients and ageing, various ageing-related concepts and indices were used (e.g., frailty, sarcopenia, successful ageing as lack of diseases, physical or cognitive functioning) but the results seemed to be inconclusive. Low protein and low fat intake were related with prevalence of frailty and sarcopenia [18][19][20]. In some prospective studies, dietary protein intake was related to better ageing-related indices [15,[21][22][23], but not in all [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of the included studies are shown in Table 1 . Five cross-sectional studies [ 31 , 32 , 33 , 34 , 35 ], one longitudinal study [ 36 ], and one case-control study [ 37 ] that investigated 3353 community-dwelling older adults with a mean age of approximately 73 years from Australia, Belgium, Finland, India, and the Netherlands were included. One study [ 32 ] included participants from Italy, Poland, the Netherlands, and the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…Sarcopenia was operationalized according to the European Working Group on Sarcopenia in Older People (EWGSOP) [ 1 ], EWGSOP2 [ 2 ], and the Foundation for the National Institutes of Health (FNIH) sarcopenia project [ 5 ]. One study compared all three sarcopenia frameworks [ 34 ], and one study [ 32 ] diagnosed sarcopenia according to the presence of low skeletal muscle index (SMI) and SPPB score.…”
Section: Resultsmentioning
confidence: 99%